Gynaecological morbidities and health seeking behaviour of aged tribal women in Trivandrum district, Kerala, India - Babu, Asha Jaya; Radha, Sreekumari; Nambisan, Bindu; Brahmanandan, Maya Devi (International Journal Of Community Medicine And Public Health, 2016)
Background: Gynaecological morbidities is any condition, disease or dysfunction of the reproductive system that is not associated with pregnancy which include reproductive tract infections, cervical cell changes, prolapse, urinary tract infection, back pain due to osteoporosis. The community based prevalence of gynaecological morbidities are influenced by demographic, social, cultural and behavioural factors. Geriatric gynaecological problem especially in tribal population has not received adequate attention in India. It is a fact that, health seeking behaviour forms an important component in formulating health programs as successful interventions depends on the accessibility and acceptability ,both of which relates to social factors. The objective of this study was to assess the gynaecological morbidities of aged (>60 years) tribal women in Trivandrum district living in various settlement areas and also to study their health seeking behavior. Methods: 11 panchayats were selected where the density of tribal population was high, and using cluster sampling method, a sample size of119 was arrived at, and these many women were included in this study out of the total of 2362 aged tribal women residing in Trivandrum. 12 camps were conducted in settlement areas during the period of one year of study. Socio-demographic, general health, and gynaecological examination was conducted and findings noted in a proforma. Results: 47.1% women had one or more coexistent gynaecological morbidities. 16% had clinical evidence of vaginitis, 9.2% had urinary tract infection, 12.6% had prolapse of some degree, 3.4% had cervical lesions. 80% of tribal women belonged to low socio economic status. 74.8% tribal women were anaemic. However around 80% had health seeking behaviour. The rest did not seek because of inaccessibility or shyness to discuss gynaecological morbidities. Conclusions: Aged trial women harbour considerable gynaecological morbidities. Inspite of having a very high level of health seeking behaviour it was noted in the current study that the prevalence of anaemia was very high. Therefore there is an urgent need to further improve health facilities and health care in these areas.